Do Independent Commissioners and Ownership Structure Influence Sustainability Report Disclosure in Indonesia? - Pratitarari, Avi Atmalistya; Honggowati, Setianingtyas (Universitas Negeri Semarang, 2025)
Purpose: The study examines the influence of Independent Commissioners and ownership structure (managerial, institutional, and foreign ownership) on sustainability disclosure in Indonesian energy, transportation, and industrial sector companies during 2021–2022. Method: The study uses secondary data from 111 companies in Indonesia’s energy, transportation, and industrial sectors during 2021–2022. Multiple linear regression analysis examines the impact of Independent Commissioners and ownership structure on sustainability report disclosure. Findings: The results show that Independent Commissioners and ownership structure (managerial, institutional, and foreign ownership) have significant positive impact on sustainability disclosure. These findings align with agency theory, emphasizing the role of governance mechanisms in enhancing transparency and accountability. Novelty: Unlike previous studies using Environmental, Social, and Economic Disclosure Scores, this research adopts the updated GRI Standards 2021 index, which emphasizes both performance and long-term sustainability commitments. By incorporating four corporate governance proxies (Independent Commissioners, managerial, institutional, and foreign ownership) the study offers a more comprehensive view of ownership influence. Focusing on the 2021–2022 period, it provides timely insights into current corporate reporting practices in Indonesia.